Longer-term increased cortisol levels in young people with mental health problems. (28th February 2016) - Heinze, Kareen; Lin, Ashleigh; Reniers, Renate L.E.P.; Wood, Stephen J.
Abstract: Disturbance of hypothalamus–pituitary–adrenal axis activity is commonly reported in a range of mental disorders in blood, saliva and urine samples. This study aimed to look at longer-term cortisol levels and their association with clinical symptoms. Hair strands of 30 young people (16–25 years) presenting with mental health problems ( M age ±SD=21±2.4, 26 females) and 28 healthy controls (HC, M age ±SD=20±2.9, 26 females) were analyzed for cortisol concentrations, representing the past 6 months prior to hair sampling. Clinical participants completed an assessment on psychiatric symptoms, functioning and lifestyle factors. All participants completed the Perceived Stress Scale. Hair cortisol concentrations representing the past 3 (but not 3–6) months were significantly increased in clinical participants compared to HC. Perceived stress in the past month was significantly higher in clinical participants compared to HC, but not significantly correlated with hair cortisol. Hair cortisol levels were not significantly associated with any other measures. Hair segment analyses revealed longer-term increased levels of cortisol in the past 3 months in early mental health problems. Further insight into the role of cortisol on the pathogenesis of mental illnesses requires longitudinal studies relating cortisol to psychopathology and progression of illness. Highlights: Investigation of hair cortisol in young people with mental health problems. Elevated first segment cortisol in clinical participants compared to controls. Hair cortisol was not associated with clinical measures.